Further evidence of tetragonality in bainitic ferrite. (January 2015) - Hulme-Smith, C. N.; Peet, M. J.; Lonardelli, I.; Dippel, A. C.; Bhadeshia, H. K. D. H.
<x content-type="archive" xml:space="preserve">Abstract</x> There is growing evidence that bainitic ferrite which retains a substantial amount of carbon in solid solution does not have cubic symmetry. We provide additional data on a different nanostructured bainitic steel to support this evidence, based on synchrotron X-ray diffraction experiments. The data are consistent only with a displacive transformation mechanism for bainite.